Choroby postihující kůži kštice - Suchánková, Dana (Casopis lekaru ceskych, 2017)
The skin of the scalp differs from the skin on the other areas of the body because of a higher density of hair follicles and higher sebum production. These, together with the presence of hair, provide a suitable environment for superficial infections, infestations and inflammatory diseases. The good condition of the scalp has a significant impact on the patient's mental well-being and social interaction. The visibility of this part of the skin and the presence of hair itself restrict the range of possible therapeutic agents that can be used due to the complicated application and poor cosmetic outcome. That is the reason why different galenic forms are usually chosen for the scalp compared to the other sites of the skin. The article provides an overview of the most common scalp disorders, the diagnostic approach and recommendations for the treatment.
Keywords: tinea capitis; lice infestations; atopic dermatitis contact dermatitis.; psoriasis; seborrheic dermatitis; Tinea Capitis; seboroická dermatitida; lidé; skalp; Psoriasis; Scalp; psoriáza; Humans; Dermatitis, Seborrheic; dermatózy skalpu; Scalp Dermatoses